2005
DOI: 10.1007/s00213-005-2171-0
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid CB1 antagonist AM 251 produces food avoidance and behaviors associated with nausea but does not impair feeding efficiency in rats

Abstract: The CB1 antagonist AM 251 may reduce food intake in part by inducing nausea or malaise, but not because of incoordination or motor slowing related to feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
115
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(126 citation statements)
references
References 45 publications
9
115
2
Order By: Relevance
“…SR141716 potentiated lithium chloride-induced conditioned rejection reactions in rats , and this drug also produced emesis in the least shrew (Darmani, 2001) and nausea in humans (Despres et al, 2005). Although rats do not vomit, recent studies from our laboratory demonstrated that administration of AM251 led to the production of conditioned gaping in rats (McLaughlin et al, 2005b), which is thought to be a selective marker of nausea in that species (Parker et al, 1998;Parker and Limebeer, 2006). These gaping responses are elicited by treatments that produce vomiting in emetic species (Parker et al, 1998), and treatments that attenuate toxin-induced vomiting in emetic species also attenuate toxin-induced conditioned gaping in rats Parker, 2000, 2003;Limebeer et al, 2004; for a review, see Parker et al, 2003).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…SR141716 potentiated lithium chloride-induced conditioned rejection reactions in rats , and this drug also produced emesis in the least shrew (Darmani, 2001) and nausea in humans (Despres et al, 2005). Although rats do not vomit, recent studies from our laboratory demonstrated that administration of AM251 led to the production of conditioned gaping in rats (McLaughlin et al, 2005b), which is thought to be a selective marker of nausea in that species (Parker et al, 1998;Parker and Limebeer, 2006). These gaping responses are elicited by treatments that produce vomiting in emetic species (Parker et al, 1998), and treatments that attenuate toxin-induced vomiting in emetic species also attenuate toxin-induced conditioned gaping in rats Parker, 2000, 2003;Limebeer et al, 2004; for a review, see Parker et al, 2003).…”
Section: Introductionmentioning
confidence: 81%
“…CB1 receptors are present in the brain stem dorsal vagal complex, and CB1 receptors in this area are associated with triggering emetic responses (Van Sickle et al, 2003). Conditioned taste avoidance can be produced by administration of the CB1 inverse agonists SR141716 (De Vry et al, 2004) and AM251 (McLaughlin et al, 2005b). SR141716 potentiated lithium chloride-induced conditioned rejection reactions in rats , and this drug also produced emesis in the least shrew (Darmani, 2001) and nausea in humans (Despres et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations